Game Narratives as Tools for Shaping Political Discourse Amidst Information Wars: The Case of the Ukrainian Conflict - Daniil A. Fedotov; Stanislav I. Kaminsky (RUDN Journal of Political Science, 2025)
The video games are a significant tool for influencing the processes of transformation of mass consciousness through interactive symbols and narratives. The political images of Russia built into their structure are identified and systematized, and strategic approaches to preventing information risks and optimizing socio-political communications are developed. The empirical material of the study includes foreign video games released between 2014 and 2024, containing direct references to events taking place in Ukraine. The methodology of the study is based on the synthesis of narrative, semiotic and discourse analysis of game annotations, algorithmic study of game mechanics, expert assessments and longitudinal monitoring. The results of the study revealed a significant transformation of the representation of the conflict in the video game space. Until 2014, the Ukrainian segment of the foreign gaming industry maintained cultural and thematic ties with the post- Soviet space, but in subsequent years the vector of narratives shifted towards the formation of an antagonistic image of Russia. Games released after 2022 have systematically introduced anti- Russian symbols, indicating that video games have become an effective tool for information warfare. As a strategic response to these challenges, the authors propose a comprehensive program for the development of the Russian gaming industry. It includes a number of key initiatives: the creation of grant programs aimed at developing patriotically oriented gaming projects; the integration of educational elements into game mechanics; the expansion of international cooperation within the BRICS and SCO; as well as legal regulation of political content in video games. The comprehensive implementation of these measures is aimed at strengthening Russia’s digital sovereignty in the context of modern geopolitical turbulence.